IWGDF guidance on the diagnosis and management of foot infections in persons with diabetes. (January 2016) - Lipsky, Benjamin A.; Aragón‐Sánchez, Javier; Diggle, Mathew; Embil, John; Kono, Shigeo; Lavery, Lawrence; Senneville, Éric; Urbančič‐Rovan, Vilma; Van Asten, Suzanne; ,
Recommendations: Classification/diagnosis: Diabetic foot infection must be diagnosed clinically, based on the presence of local or systemic signs or symptoms of inflammation (strong; low). Assess the severity of any diabetic foot infection using the Infectious Diseases Society of America/International Working Group on the Diabetic Foot classification scheme (strong; moderate). Osteomyelitis: For an infected open wound, perform a probe‐to‐bone test; in a patient at low risk for osteomyelitis, a negative test largely rules out the diagnosis, while in a high‐risk patient, a positive test is largely diagnostic (strong; high). Markedly elevated serum inflammatory markers, especially erythrocyte sedimentation rate, are suggestive of osteomyelitis in suspected cases (weak; moderate). A definite diagnosis of bone infection usually requires positive results on microbiological (and, optimally, histological) examinations of an aseptically obtained bone sample, but this is usually required only when the diagnosis is in doubt or determining the causative pathogen's antibiotic susceptibility is crucial (strong; moderate). A probable diagnosis of bone infection is reasonable if there are positive results on a combination of diagnostic tests, such as probe‐to‐bone, serum inflammatory markers, plain X‐ray, magnetic resonance imaging (MRI) or radionuclide scanning (strong; weak). Avoid using results of soft tissue or sinus tract specimens for selecting antibiotic therapy for osteomyelitis as they do not accurately reflect bone culture results (strong; moderate). Obtain plain X‐rays of the foot in all cases of non‐superficial diabetic foot infection (strong; low). Use MRI when an advanced imaging test is needed for diagnosing diabetic foot osteomyelitis (strong; moderate). When MRI is not available or contraindicated, consider a white blood cell‐labelled radionuclide scan, or possibly single‐photon emission computed tomography (CT) and CT (SPECT/CT) or fluorine‐18‐fluorodeoxyglucose positron emission tomography/CT scans (weak; moderate). Assessing severity: At initial evaluation of any infected foot, obtain vital signs and appropriate blood tests, debride the wound and probe and assess the depth and extent of the infection to establish its severity (strong; moderate). At initial evaluation, assess arterial perfusion and decide whether and when further vascular assessment or revascularization is needed (strong; low). Microbiological considerations: Obtain cultures, preferably of a tissue specimen rather than a swab, of infected wounds to determine the causative microorganisms and their antibiotic sensitivity (strong; high). Do not obtain repeat cultures unless the patient is not clinically responding to treatment, or occasionally for infection control surveillance of resistant pathogens (strong; low). Send collected specimens to the microbiology laboratory promptly, in sterile transport containers, accompanied by clinical information on the type of specimen and location of the wound (strong; low). Surgical treatment: Consult a surgical specialist in selected cases of moderate, and all cases of severe, diabetic foot infection (weak; low). Perform urgent surgical interventions in cases of deep abscesses, compartment syndrome and virtually all necrotizing soft tissue infections (strong; low). Consider surgical intervention in cases of osteomyelitis accompanied by spreading soft tissue infection, destroyed soft tissue envelope, progressive bone destruction on X‐ray or bone protruding through the ulcer (strong; low). Antimicrobial therapy: While virtually all clinically infected diabetic foot wounds require antimicrobial therapy, do not treat clinically uninfected wounds with antimicrobial therapy (Strong; Low) Select specific antibiotic agents for treatment based on the likely or proven causative pathogens, their antibiotic susceptibilities, the clinical severity of the infection, evidence of efficacy of the agent for diabetic foot infection and costs (strong; moderate). A course of antibiotic therapy of 1–2 weeks is usually adequate for most mild and moderate infections (strong; high). Administer parenteral therapy initially for most severe infections and some moderate infections, with a switch to oral therapy when the infection is responding (strong; low). Do not select a specific type of dressing for a diabetic foot infection with the aim of preventing an infection or improving its outcome (strong; high). For diabetic foot osteomyelitis, we recommend 6 weeks of antibiotic therapy for patients who do not undergo resection of infected bone and no more than a week of antibiotic treatment if all infected bone is resected (strong; moderate). We suggest not using any adjunctive treatments for diabetic foot infection (weak; low). When treating a diabetic foot infection, assess for use of traditional remedies and previous antibiotic use and consider local bacterial pathogens and their susceptibility profile (strong; low).